Interventions for Caregivers Caring for a Family Member With Advanced Illness at Home: A Systematic Review - Sevillano‐Garayoa, Leire; Olano‐Lizarraga, Maddi; Martín‐Martín, Jesús (Nursing & health sciences, 2025)
ABSTRACT The rising prevalence of advanced illness poses growing challenges for family caregivers, requiring healthcare professionals to address an increasing array of caregiver needs. This systematic review explores the impact of at‐home interventions for caregivers supporting individuals with advanced illness, examining intervention characteristics and methodological quality. Quantitative studies published over the past 5 years (2019–2024) were sourced from PubMed, PsycINFO, CINAHL, Scopus, and Cochrane Library. Intervention data, including modality, components, timing, providers, recipients, and caregiver outcomes, were systematically reviewed. Methodological quality was assessed using Cochrane RoB 2 and ROBINS‐I. From 16 studies, key caregiver needs such as depression, anxiety, distress, quality of life, burden, and caregiving self‐efficacy emerged as primary areas addressed. The majority of interventions were face‐to‐face, nurse‐led, and aimed at primary caregivers. Findings underscore the importance of personalized interventions that consider caregivers' unique responses and actively involve them in design. Nurses play a crucial role in leading these interventions, positioning them as central to enhancing caregiver support in home settings.